2019
DOI: 10.1021/acs.jmedchem.9b00876
|View full text |Cite
|
Sign up to set email alerts
|

Homodimeric Tobramycin Adjuvant Repurposes Novobiocin as an Effective Antibacterial Agent against Gram-Negative Bacteria

Abstract: Low permeability across the outer membrane is a major reason why most antibiotics are ineffective against Gram-negative bacteria. Agents that permeabilize the outer membrane are typically toxic at their effective concentrations. Here, we report the development of a broad-spectrum homodimeric tobramycin adjuvant that is nontoxic and more potent than the gold standard permeabilizing agent, polymyxin B nonapeptide. In pilot studies, the adjuvant confers potent bactericidal activity on novobiocin against Gram-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 55 publications
4
48
0
Order By: Relevance
“…We found that the MICs of tobramycin across these isolates were identical ( Table 5), suggesting that compound 1 does not trigger resistance development to aminoglycosides. This observation is consistent with a previous report on studies with A. baumannii (34).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…We found that the MICs of tobramycin across these isolates were identical ( Table 5), suggesting that compound 1 does not trigger resistance development to aminoglycosides. This observation is consistent with a previous report on studies with A. baumannii (34).…”
Section: Resultssupporting
confidence: 94%
“…To investigate whether ceftolozane suffers from either of the intrinsic resistance mechanisms of outer membrane permeability and efflux, we assessed its potency, alone and in combination with compound 1, against efflux-competent MDR and efflux-deficient P. aeruginosa isolates. Compound 1, a molecule derived by dimerization of short-chain amphiphilic tobramycins, has been previously reported as a nontoxic and more potent outer membrane permeabilizer than polymyxin B nonapeptide (PMBN) (34). A checkerboard assay was therefore used to assess the interactions between ceftolozane and compound 1, and the results were interpreted as a function of the fractional inhibitory concentration index (FICI) (42).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other conjugates were prepared in as imilar way by using polymyxin B, which is am embrane-targeting decalipopeptide antibiotic used to treat MDR/XDR Gram-negative bacterial infections. [118] Rifampicin-5 conjugates werea lso prepared to break the intrinsic resistance and sensitize multidrug and extensively drug-resistant P. aeruginosa to doxycycline and chloramphenicol in vitro and in vivo. [119] Conjugation of 5 to cyclam abrogated the ribosomale ffects of 5,b ut conferredapotent adjuvant property that restored full antibiotic activity of meropenem and aztreonam against carbapenem-resistant P. aeruginosa.…”
Section: Lipid Conjugatesmentioning
confidence: 99%